Penerapan Good Governance dan Pengendalian Internal dalam Meningkatkan Kinerja Pengelolaan Keuangan di Polrestabes Palembang - Tania; Fitriasuri (Ikatan Da'i Indonesia, 2025)
The implementation of the concept of Good Governance and a systematic internal control framework is expected to improve the performance of financial management in the Palembang Police environment. Although various provisions and guidelines on Good Governance and SPIP have been available, findings in the field still found various obstacles related to consistency of implementation, transparency of information, accountability, synergy between units, and optimal use of information technology.